Increase of Magnetic Sensitivity of Magnetically Controlled MEMS Switches. Issue 34 (23rd May 2016) - Karabanov, Sergey M.; Suvorov, Dmitry V.; Gololobov, Gennady P.; Tarabrin, Dmitry Y.; Slivkin, Evgeny V.
ABSTRACT: The paper presents the research results of influence of various parameters of magnetic field concentrator geometry on sensitivity of magnetically controlled MEMS switches. It is shown that magnetic sensitivity increases with the growth of the magnetic concentrator width and practically does not depend on its length. It is established that dependence of magnetic sensitivity on the overlap length of the ferromagnetic flexible contact-concentrator has a minimum corresponding to 2-3 lengths of the contact gap. Recommendations on sensitivity increase of magnetically controlled MEMS switches are provided.